2021
DOI: 10.1002/pc.26156
|View full text |Cite
|
Sign up to set email alerts
|

A silicon rubber composite with enhanced thermal conductivity and mechanical properties based on nanodiamond and boron nitride fillers

Abstract: Silicone rubber (SR) is a nonreactive and stable material that is widely applied in a wide variety of products including electrical and electronic appliances.Currently, the synthesis of SR with enhanced thermal conductivity and mechanical properties is of great significance. Herein, an improved thermal conductive SR composite was synthesized by using nanodiamond (ND) and boron nitride (BN) as composite thermal conductivity fillers to the terminal hydroxyl functional group of SR. We studied the thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…In order to understand the relationship of mechanical properties of nanocomposites with the molecular architecture and interactions between the polymeric chains chain, we have endeavored to further analyze the actual enhancement mechanism responsible for the improvement in the mechanical properties of the nanocomposites. As suggested by previous researchers, [ 30–34 ] the improved mechanical properties of polymer‐BNNP nanocomposites primarily resulted from a stronger interfacial bonding interaction between fillers and polymer matrix, brought about by the treatment with surfactants. However our work, the enhancement of mechanical properties of nanocomposites can be mainly attributed to the formation of partially stretched HDPE chains during the twin‐screw extrusion process and the “sunflower‐like” core‐shell structure of HDPE‐BNNP nanocomposites.…”
Section: Resultsmentioning
confidence: 73%
“…In order to understand the relationship of mechanical properties of nanocomposites with the molecular architecture and interactions between the polymeric chains chain, we have endeavored to further analyze the actual enhancement mechanism responsible for the improvement in the mechanical properties of the nanocomposites. As suggested by previous researchers, [ 30–34 ] the improved mechanical properties of polymer‐BNNP nanocomposites primarily resulted from a stronger interfacial bonding interaction between fillers and polymer matrix, brought about by the treatment with surfactants. However our work, the enhancement of mechanical properties of nanocomposites can be mainly attributed to the formation of partially stretched HDPE chains during the twin‐screw extrusion process and the “sunflower‐like” core‐shell structure of HDPE‐BNNP nanocomposites.…”
Section: Resultsmentioning
confidence: 73%
“…It has been observed that the combination of various thermally conductive fillers makes it easier to form an efficient thermally conductive network synergistically in the matrix owing to the synergistic effect of different thermally conductive fillers, eventually improving the thermal conductivity of polymer-based composites 50,101,102,109–121 (Table 5). The thermal conductivity of the epoxy resin composite was enhanced at a thermally conductive filler loading of 42 wt% (the ratio of AlN and BN = 2 : 1), the thermal conductivity of which was 0.57 W m −1 K −1 .…”
Section: Influencing Factors On the Thermal Conductivity And Developm...mentioning
confidence: 99%
“…As a result, the heat accumulation and heat flux in electrical equipment both rise. [ 1–4 ] To ensure cruising time and operational durability of electronic equipment, it is putting forward severer requirements to dissipate heat. [ 5,6 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the heat accumulation and heat flux in electrical equipment both rise. [1][2][3][4] To ensure cruising time and operational durability of electronic equipment, it is putting forward severer requirements to dissipate heat. [5,6] Thermal conductive composites are one of the most promising types of polymer-based composites for thermal management in current electrical applications that demand high thermal conductivity (TC), remarkable thermal stability, and superior electrical insulation.…”
Section: Introductionmentioning
confidence: 99%